Narrating Mother Identities From Prison. (December 2019) - Easterling, Beth A.; Feldmeyer, Ben; Presser, Lois
Incarcerated mothers face challenges to mothering in prison, including restricted opportunities to perform parenting tasks, ambiguous loss, and a compromised parenting identity. This study uses interviews with incarcerated mothers in the United States to explore how such women negotiate motherhood. All of the women grappled with how to care for their children from prison and projected futures that they hoped to experience as mothers. They varied in their active involvement as decision makers and in their intimacy with their children, but all were seen as renegotiating narrative identities. The study underscores the fact that social actors can be creative with self-narrative when they can be creative in few other ways.